Next generation antibody drug conjugates (ADCs) and immunotoxins - Grawunder, Ulf; Barth, Stefan (Springer, 2017)
This book describes the newest developments in antibody drug conjugates and immunotoxins, paving their way to clinical application. Lessons learned from the current state of the art are used to further improve our understanding of their mechanisms of action and off target activities. The book introduces scientists to all of the prerequisites that must be properly addressed, including identification of the right target, specific traits of target binding antibodies, proper selection of the toxic payload, internalization induced by binding, and next generation conjugation and linker technologies. These knowledge-based, revolutionary new drug principles will form the cornerstone of the future standard of care and will lead to major advances in application, as well as improved quality of life and patient survival rates. This book will be of interest to biotech companies and researchers working in the fields of immunology, pharmacology, and oncology.- Resumé vydavatel
Keywords: imunofarmakologie; monoklonální protilátky; onkologie; farmakoterapie; immunopharmacology; monoclonal antibodies; oncology; pharmacotherapy; elektronické knihy; sborníky; electronic books; papers of several authors